Chapter 2: Modelling transition-related shocks in the green economy - Jackson, Andrew (Edward Elgar Publishing, 2024)
Limiting global temperature increases to 2°C above pre-industrial levels will necessitate a transition away from fossil fuels and towards low-carbon forms of energy production. While an energy technology transition is necessary to avoid the catastrophic effects of climate change, the transition and its drivers may also generate a number of transition risks, including asset stranding. This chapter presents a stock-flow consistent, input–output model for the study of the different shocks associated with different transitions to a low-carbon economy. These shocks include the introduction of a carbon tax, a change in bank-financing conditions, a change in the energy sector’s production processes and changes in social norms. The results of these simulations suggest that shocks that affect the real side of the economy are likely to lead to larger impacts on demand and generate larger transition risks than those that primarily affect firms’ borrowing costs.